Karakterisasi asap cair dari serasah daun kering di lingkungan Universitas Lampung [Characterization of liquid smoke from dry leaf litter in Lampung University] - Suroso, Erdi; Al Rasyid, Harun; Utomo, Tanto Pratondo; Ritonga, Dinda Nur Annisa; Anungputri, Pramita Sari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
One solution to reduce leaf litter is to process it into liquid smoke. This study aimed to determine the characteristics of liquid smoke from various types of dry leaves. The type of leaves used in this study were teak, fern, Spanish cherry, and crepe myrtle-dried leaves. Treatment of pyrolysis gave three types of products. The smoke liquid yields of dried teak leaves were 12,44%, dried Spanish cherry leaves were 12.92%, dried fern leaves were 13,39%, and dried crape myrtle leaves were 35.22%. The charcoal yields from teak, fern, Spanish cherry, and crape myrtle-dried leaves were 40.585%, 35.871%, 40.723%, and 18.797%. While the rest was tar with yields of 0.820% from dried teak leaves, 0.869% from dried fern leaves, 0.790% from dried Spanish cherry leaves, and 1.774% from dried crape myrtle leaves. The residual dry leaf debris of dried teak was 53.938%, dried fern leaves 51.385%, dried Spanish cherry leaves 54.326%, and dried crape myrtle leaves 54.210%. The pH of smoke liquor from dried teak was 5.11, dried fern leaves 5.75, dried Spanish cherry leaves 5.43, and dried crape myrtle leaves 7.80. The dominant active compounds in the liquid smoke produced were phenolic components. Each liquid smoke contained carbonyl and acid compounds, while liquid smoke from teak-dried leaves also contained alkaloids and alcohol.